2015
DOI: 10.1111/ppl.12398
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial role of spermidine in chlorophyll metabolism and D1 protein content in tomato seedlings under salinity–alkalinity stress

Abstract: Polyamines are important in protecting plants against various environmental stresses, including protection against photodamage to the photosynthetic apparatus. The molecular mechanism of this latter effect is not completely understood. Here, we have investigated the effects of salinity-alkalinity stress and spermidine (Spd) on tomato seedlings at both physiological and transcriptional levels. Salinity-alkalinity stress decreased leaf area, net photosynthetic rate, maximum net photosynthetic rate, light saturat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 42 publications
3
30
0
Order By: Relevance
“…Reports discussing the combined effects of Kn and Spd on the chlorophyll synthesis and photosynthesis are not available. In tomato exposed to salinity-alkalinity stress, Hu et al [58] have demonstrated increased D1 protein synthesis and amelioration of the decline in photosynthesis due to the exogenous treatment of Spd. In addition, exogenous Spd application reduces chlorophyll degradation and enhances the stabilization of chloroplast structures [26].…”
Section: Discussionmentioning
confidence: 99%
“…Reports discussing the combined effects of Kn and Spd on the chlorophyll synthesis and photosynthesis are not available. In tomato exposed to salinity-alkalinity stress, Hu et al [58] have demonstrated increased D1 protein synthesis and amelioration of the decline in photosynthesis due to the exogenous treatment of Spd. In addition, exogenous Spd application reduces chlorophyll degradation and enhances the stabilization of chloroplast structures [26].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, it was shown that salinity stress effects on chlorophyll metabolism could be alleviated by supplementation with spermidine (Hu et al . ), putrescine (Yuan et al . ) or cytokinin (Krishna et al .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the prevention of electron transfer from the primary acceptor Q A to the secondary acceptor Q B would form the triplet chlorophyll ( 3 P680) which, when combined with oxygen, would generate singlet oxygen ( Fig 4 ). The singlet oxygen could cause D1 protein, important in repair, to be degraded and cause pigment decomposition, directly inhibiting photosynthesis [ 36 , 37 ]. GABA, which appears to stabilize the photosynthetic electron transport chain and the photosynthetic apparatus ( Fig 8 ), may enhance the activity of superoxide dismutase, accelerate ascorbic acid-glutathione cycling, and increase the content of antioxidants that scavenge ROS, leading to stabilization of the structure and function of chloroplast[ 22 , 38 ].…”
Section: Discussionmentioning
confidence: 99%